Arahan Penataan Tepian Air di Kawasan Waduk Tunggu Bitowa, Kelurahan Bitowa, Kecamatan Manggala, Kota Makassar - Adhiem Muksid Rasal; Mukti Ali; Sri Aliah Ekawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2022)
The Waiting Bitowa Reservoir is designated as a local protected area that functions to protect the sustainability of raw water sources, terrestrial ecosystems, regional environmental balance, creating a balance between the natural environment and the built environment that is useful for the benefit of the community. The banks of the reservoir are also often used by the community to interact and carry out other public activities. However, the existing facilities to support community activities are not yet optimal because there are several potentials that have not yet been developed. Therefore, this study aims to identify existing conditions, analyze problems and potentials, and formulate directions for public spatial planning in the Waiting Bittowa Reservoir Area. This research uses spatial analysis, Likert scale and importance performance analysis (IPA). This research lasted for six months, from February to June 2021. The results of this study show that the existing conditions indicate that the public space area has not optimally supported community activities, while the problems found were the unavailability of signboards/information and parking lots, conditions potholed and narrow roads, no pedestrian paths, and no embankments. This area has the potential because it has the charm and activity of shamans. The directives are in the form of procuring signboards and information, repairing Jalan Toddopuli and Borong, providing parking lots and building embankments for preservation purposes.